Clinical sensitivity and specificity of serum total bilirubin – A study on thyroid status in clinically euthyroid non-obese, overweight, and obese type 2 diabetics - Jayanthi, Rajendran; Srinivasan, Abu Raghavan; Maran, Anandhraj Lokesh (International Journal of Health Sciences, 2019)
Objective: The objective of this study was to evaluate the sensitivity and specificity of total bilirubin (serum) in determining thyroid status in clinically euthyroid non-obese, overweight, and obese type 2 diabetics. Subjects and Methods: Three anthropometry specific groups of clinically euthyroid type 2 diabetics were enabled, following enrolment: 153 non-obese (body mass index [BMI] = 18.5–24.99), 291 overweight (BMI = 25–29.99), and 126 obese type 2 diabetes mellitus (BMI ≥30). Total bilirubin (serum), glycemic status, insulin resistance (IR), and thyroid hormones, besides routine biochemistry, were estimated, as per International Federation of Clinical Chemistry approved procedures. Results: Receiver operating characteristic curves for non-obese, overweight, and obese were plotted to assess the role of total bilirubin (serum) in determining thyroid status in clinically euthyroid type 2 diabetics. In overweight, the area under curve (AUC) for FT3 and postprandial sugar showed 0.621 and 0.531 with cutoff values of 2.02 pg/ml and 147.5 mg/dl, respectively, whereas for aspartate aminotransferase/alanine aminotransferase (De Ritis ratio), the AUC was 0.583. As regards, obese diabetics and the AUC for insulin and homeostatic model assessment IR were 0.657 and 0.709, respectively, with cutoff values of 16.06 mIU/L and 7.274, respectively, and for postprandial sugar 0.727, in the same group (obese) with cutoff value of 208.5 mg/dl. Conclusion: Total bilirubin could predict thyroid status and IR in anthropometry specific clinically euthyroid type 2 diabetics.